Upaya Brand Salience untuk Mendorong Terjadinya Brand Resonance - Hariyadi, Guruh Taufan; Nuryanto, Imam; Wijaya, Michaela Pratiwi (Jurnal Penelitian Ekonomi dan Bisnis, 2020)
This study aims to examine an integrated model of brand salience, perceived quality, buying decision, brand feeling, and brand resonance to the readers of Suara Merdeka Newspaper in Semarang. The sample of this study was 135 readers of Suara Merdeka Newspaper in Semarang. Exogenous and endogenous measurements have been approved using confirmatory analysis. Furthermore, it is analyzed with the Structural Equation Model to examine the causality relationship between the variables that influence and are measured by brand salience, purchasing decisions, perceived quality, brand feelings and brand resonance. Conclusions from the results of this study indicate that to increase brand resonance can be obtained through brand feelings obtained from the confidence of the purchase results due to brand excellence (Brand Salience).Keywords: : Brand Resonance; Brand Salience; Brand Feeling; buying decision; Perceived Quality 3Penelitian ini bertujuan untuk menguji model terintegrasi brand salience, perpsepsi kualitas, keputusan pembelian, brand feeling, brand resonance kepada para pembaca Surat Kabar Suara Merdeka di Semarang. Sampel penelitian ini adalah 135 pembaca Surat Kabar Suara Merdeka di Semarang. Pengukuran eksogen dan endogen telah diuji dengan menggunakan analisis konfirmatori. Selanjutnya dianalisis dengan Structural Equation Model untuk pengujian hubungan kausalitas antar variabel-variabel yang mempengaruhi dan dipengaruhi oleh brand salience, keputusan pembelian, perceived quality, brand feeling dan brand resonance. Simpulan dari hasil penelitian ini menunjukkan bahwa untuk meningkatkan Brand Resonance dapat dicapai melaui Brand Feeling yang diperoleh dari keyakinan keputusan pembelian karena kemenonjolan merek (Brand Salience).Kata Kunci: Brand Resonance; Brand Salience; Brand Feeling; Keputusan Pembelian; Perceived Quality